Reduction of TSS and ammonia in the tofu liquid waste by combined process biofilter mediated plastic and water plants for media of fish life - Agus Amsah; Budijono '; M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in September-December 2013 in the factory know which is located on Jl. Build Kubang Kingdom Village Tarai Mining District of Kampar district in Riau Province. The purpose of this study was to determine the effectiveness of a decrease in TSS and ammonia wastewater know. The decrease in the concentration of TSS and ammonia made with plastic bottles of media biofilter system anaerobic-aerobic process plastic scrap plastic pieces containing medium and without (controls). Then proceed with the process of phytoremediation by water hyacinth and without media. The combined performance of the biofilter and phytoremediation of media is very effective to reduce the concentration of TSS and ammonia. This is evident from a decrease in the effectiveness of the TSS concentration during the observations ranged from 66.38 to 90.82% with an average concentration at the inlet of 411.4 mg / l to 57.2 mg / l. While the effectiveness of the reduction in ammonia concentrations ranged from 54.74 to 92.56% with an average concentration at the inlet of 13.16 mg / l to 4.28 mg / l. For other parameters also are in accordance with the quality standards that have been established, such as pH 7, temperature 28 0C, and DO of 3.76 mg / l. Further tests of the survival of fish and tilapia on the marsh Sepat wastewater that has been treated with a biofilter media and plastic bottles of water hyacinth respectively reached 87% and 70% except 47% of fish monitored.Keywords: Biofilter, phytoremediation, wastewater